A Future for the National Education Longitudinal Program - Barbara Schneider; Guan Saw; Michael Broda (SAGE Publishing, 2016)
Forty years ago, the National Center for Education Statistics initiated the national longitudinal studies program in response to congressional concern for policy-relevant information on school-to-work transitions. This program has grown substantially, and not unexpectedly, questions have arisen about its usefulness and present operation. This essay briefly describes the scope of the program and its benefits for informing knowledge and policy, including (a) racial and socioeconomic inequalities and their influence on the academic and social development of student subgroups, (b) differential schooling experiences and their impact on children's later educational and occupational outcomes, and (c) new methods for estimating statistical inferences. Despite these benefits, the program needs serious modification especially with respect to its organization and design features. Several substantive and methodological recommendations are made for improving the program's effectiveness, including widening technical expertise; reframing sample populations; adjusting intervals for data collections; embedding experiments and conducting field studies; linking longitudinal panels with other federal, state, and local collections; and developing new measures and forms of delivery.